2023
DOI: 10.17159/0379-4350/2023/v77a11
|View full text |Cite
|
Sign up to set email alerts
|

A journey of 10 years in analytical method development and environmental monitoring of pharmaceuticals in South African waters

Abstract: Apart from the studies which reported the occurrence of steroid hormones and antibiotics in wastewater treatment plants (WWTPs) back in 2004, 2007 and 2012, the evidence for monitoring of pharmaceuticals in South African water bodies intensified from 2014. Therefore, this study reviewed the analytical methods developed and applied in South Africa for the purpose of monitoring pharmaceuticals and their metabolites in water. At the same time, pharmaceuticals and their metabolites detected in South African waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…All pharmaceuticals under examination have been previously found present in South African waters . However, the extent of their occurrence in South African waterbodies and their fate have always been overlooked as most studies on their investigation focused largely on wastewater and surface water from inland sources.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All pharmaceuticals under examination have been previously found present in South African waters . However, the extent of their occurrence in South African waterbodies and their fate have always been overlooked as most studies on their investigation focused largely on wastewater and surface water from inland sources.…”
Section: Resultsmentioning
confidence: 99%
“…All pharmaceuticals under examination have been previously found present in South African waters. 6 However, the extent of their occurrence in South African waterbodies and their fate have always been overlooked as most studies on their investigation focused largely on wastewater and surface water from inland sources. This study revealed an important aspect: the same pharmaceuticals found in inland waters are carried through the rivers into the estuaries and eventually make their way into the ocean.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The high detection frequency for NSAIDs (ibuprofen and naproxen) is common in South African water systems as these are overthe-counter medications. 31,32 The decreased concentrations of these analytes in effluent samples indicated that certain amounts were eliminated during the wastewater treatment processes. For instance, neither ibuprofen nor naproxen were detected in effluent samples from WWTP 4.…”
Section: Research Articlementioning
confidence: 99%